THE EFFECTIVENESS OF USING CIRC IN IMPROVING STUDENTS’ READING COMPREHENSION AT SMP GPDI BEREA TONDANO - Hema Sirait; Paula Rombepajung; Tirza Kumayas (Program Studi Pendidikan Bahasa Inggris, 2022)
The purpose of this study was to test whether the use of collaborative comprehensive reading comprehension was effective in improving the reading comprehension of review texts for junior high school students. It was intended to provide reliable information about whether there was a difference in students' reading comprehension between the pretest and posttest. Data was collected through pre-treatment pre-test and post-treatment post-test on one of the seventh grade students of SMP GPDI BEREA TONDANO for the academic year 2021/2022. According to the survey data, the pre-test had a minimum score of 5 and a maximum score of 60.5. In the post hoc test, the lowest percentage was 20 and the highest percentage was 92. The results showed that the posttest average was 55.9 higher than the pretest average was 23.05. Based on these results, it can be concluded that Cooperative Integrated Reading Composition (CIRC) reading text learning was effective in improving the reading comprehension of 7th graders in recalculated texts.